Pharmacokinetics of tolbutamide and its metabolite 4‐hydroxy tolbutamide in poloxamer 407‐induced hyperlipidemic rats. (4th March 2014) - Choi, Mi Ran; Kwon, Mi Hye; Cho, Yong Yeon; Choi, Hye Duck; Kim, Yu Chul; Kang, Hee Eun
ABSTRACT Under hyperlipidemic conditions, there are likely to be alterations in the pharmacokinetics of CYP2C11 substrates following decreased expression of CYP2C11, which is homologous to human CYP2C9. The pharmacokinetics of tolbutamide (TB) and its metabolite 4‐hydroxy tolbutamide (4‐OHTB) were evaluated as a CYP2C11 probe after intravenous and oral administration of 10 mg/kg tolbutamide to poloxamer 407‐induced hyperlipidemic rats (HL rats). Changes in the expression and metabolic activity of hepatic CYP2C11 and the plasma protein binding of tolbutamide in HL rats were also evaluated. The total area under the plasma concentration–time curve (AUC) of tolbutamide in HL rats after intravenous administration was comparable to that in controls due to their comparable non‐renal clearance (CLNR). The free fractions of tolbutamide in plasma were comparable between the control and HL rats. The 4‐hydroxylated metabolite formation ratio (AUC4‐OHTB/AUCTB) in HL rats was significantly smaller than that in the control rats as a result of the reduced expression of hepatic CYP2C11 (by 15.0%) and decreased hepatic CLint (by 28.8%) for metabolism of tolbutamide to 4‐OHTB via CYP2C11. Similar pharmacokinetic changes were observed in HL rats after oral administration of tolbutamide. These findings have potential therapeutic implications, assuming that the HL rat model qualitatively reflects similar changes in patients with hyperlipidemia. Since other sulfonylureas in clinical use are substrates of CYP2C9, their hepatic CLint changes have the potential to cause clinically relevant pharmacokinetic changes in a hyperlipidemic state. Copyright © 2014 John Wiley & Sons, Ltd.